Proposing a system to support crowdsourcing - Aparicio, M.; Costa, C. J.; Braga, A. S. (Workshop on Open Source and Design of Communication, OSDOC 2012, 2012)
In this paper, a conceptual framework is proposed, supported in the literature review, derived by identifying the main concepts related to crowdsourcing, as well as ways of improving group participation. We also propose a software solution that may be used to support the crowdsourcing process. This software solution is inspired by the conceptual framework.